Colaboração entre farmacêuticos e médicos: uma revisão sistemática e validação de um instrumento de avaliação - Cunha, Luiza Correia (2016)
Introduction: Since the last century, the irrational use of drugs has been considered a risk factor to health. Thus, the evidence shows that the increase of actions to ensure the optimization of pharmacotherapy, as collaboration between pharmacists and physicians, need to be studied. Objective: to validate the Portuguese in Brazil a scale to measure collaborative attitudes of professionals and students of Pharmacy and Medicine. Methods: Initially, a systematic review with the aim of identifying the clinical literature results from clinical trials of collaboration between pharmacists and doctors was performed. The search was conducted in four international databases, using descriptors such as “'collaborative attitude", “instrument”, “pharmacists” and “physicians” in different combinations. The eligibility of studies was made based on the evaluation of titles, abstracts and full texts. In the second part of the dissertation was validated a range of collaborative attitudes among physicians and pharmacists for the Portuguese of Brazil. Following the conversion and validation protocols proposed by international literature. Results: The search yielded 12 articles that met the inclusion criteria. Half of the studies (six, 50.0%) were performed in clinics. The interaction between professionals occurred through direct contact and/ or indirectly with the use of letters, standard forms, among others. In addition, six studies showed a statistically significant reduction in blood pressure levels of patients served after the collaboration between doctors and pharmacists. Changes in grammatical structures were made in order to establish cross-cultural similarity between the English and Portuguese versions. Regarding the assessment of the expert panel, six questions needed changes. Statistical data support the validation process. Conclusion: Despite the collaboration between pharmacists and physicians present significant clinical results, this issue is not adequately addressed. Thus, the use of validated instruments has the potential to be used in the evaluation of collaborative processes in multidisciplinary clinical services.